2008
DOI: 10.1016/s1808-8694(15)30745-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and evolution of nasal polyps in children and adolescents with cystic fibrosis

Abstract: The study showed a high incidence of nasal polyps in older children, who span the entire range of clinical severity, even in the absence of clinical nasal symptoms. Topical steroid therapy showed good results. An interaction among pediatricians and otolaryngologists is necessary for diagnosis and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…The study found that most of the disease occur in the central nervous system such as the spinal canal and intracranial [8]. At present, the incidence of children and adolescents is higher and the incidence of males is higher than that of females [9]. It is the performance of the corresponding parts on the nerve root pain in clinical [4].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that most of the disease occur in the central nervous system such as the spinal canal and intracranial [8]. At present, the incidence of children and adolescents is higher and the incidence of males is higher than that of females [9]. It is the performance of the corresponding parts on the nerve root pain in clinical [4].…”
Section: Discussionmentioning
confidence: 99%
“…Согласно данным зарубеж ной литературы, около 37% взрослых пациентов с муковисцидозом имеют назальные полипы [9]. Имеются единичные данные о наличии муковисци доза в педиатрической популяции пациентов, со гласно которым частота встречаемости назального полипа составляет 39,1% случаев [10]. При этом от ечественные исследователи проводят другие цифры: 84,6% детей со смешанной или респираторной фор мой заболевания имеют назальные полипы [11].…”
Section: сведения об авторахunclassified
“…Franche and coworkers [25] in Porto Alegre, the southeast Brazilian's capital in Rio Grande do Sul state, found only two out of 23 patients with bilateral polyposis and concerning nasal obstruction, nasal secretion, and headache only eight (34.8%) reported nasal obstruction, ten (43,5%) complained of nasal secretion, and none had headache. Weber and Ferrari [26] (Botucatu, Sao Paulo State) evaluated 23 patients with an average age of 6 years and 4 months, and 22% of them complained of oral breathing.…”
Section: Symptomatologymentioning
confidence: 99%
“…From 1961 to 2005, the prevalence of nasal polyposis varied from 5% to 57% [20, 24, 26–34]. This may be explained by the increased survival rate of CF patients in developed countries, by selection of patients, by size of samples, by differences of age groups studied, and mainly by the most recent routine use of nasal endoscopy as a diagnostic technique [1, 19, 20].…”
Section: Endoscopic Findingsmentioning
confidence: 99%